Customer Loyalty Indicator of Mobile Payment Application in the Financial Service Industry: A Study of LinkAja (International Journal of Scientific Research and Management (IJSRM), 2020)
Purpose – The main purpose of this journal is to analyse on performance expectation, effort expectation, social influence, facilitating condition, hedonic motivation, perceived technology security, and trust toward the customer loyalty of using LinkAja. Research limitations/implications – This research presents the sample population of 197 participants responded to the survey in Indonesia in Java area, whereby 175 out of the number defined as users of LinkAja are valid responses that have been obtained for statistical analysis. Methodology/approach - Data collection used in this journal are questionnaire and purposive sampling methods. This research has examined provided data and information through quantitative research with Multiple Linear Regression analysis method. Findings – This research found that four independent variables, i.e. effort expectation, social influence, hedonic motivation, and trust are influencing the dependent variable of customer loyalty in using LinkAja. The result shows a performance expectation, facilitating condition and perceived technology security do not significantly influence customer loyalty. Practical implications – There are 4 (four) main significant factors to maintain the customer loyalty of mobile payment application i.e. effort expectation, social influence, hedonic motivation, and trust.